Increased corneal epithelial turnover contributes to abnormal homeostasis in the Pax6(+/-) mouse model of aniridia. - Panagiotis Douvaras; Richard L Mort; Dominic Edwards; Kanna Ramaesh; Baljean Dhillon; Steven D Morley; Robert E Hill; John D West (PLoS ONE)
We aimed to test previous predictions that limbal epithelial stem cells (LESCs) are quantitatively deficient or qualitatively defective in Pax6(+/-) mice and decline with age in wild-type (WT) mice. Consistent with previous studies, corneal epithelial stripe patterns coarsened with age in WT mosaics. Mosaic patterns were also coarser in Pax6(+/-) mosaics than WT at 15 weeks but not at 3 weeks, which excludes a developmental explanation and strengthens the prediction that Pax6(+/-) mice have a LESC-deficiency. To investigate how Pax6 genotype and age affected corneal homeostasis, we compared corneal epithelial cell turnover and label-retaining cells (LRCs; putative LESCs) in Pax6(+/-) and WT mice at 15 and 30 weeks. Limbal BrdU-LRC numbers were not reduced in the older WT mice, so this analysis failed to support the predicted age-related decline in slow-cycling LESC numbers in WT corneas. Similarly, limbal BrdU-LRC numbers were not reduced in Pax6(+/-) heterozygotes but BrdU-LRCs were also present in Pax6(+/-) corneas. It seems likely that Pax6(+/-) LRCs are not exclusively stem cells and some may be terminally differentiated CD31-positive blood vessel cells, which invade the Pax6(+/-) cornea. It was not, therefore, possible to use this approach to test the prediction that Pax6(+/-) corneas had fewer LESCs than WT. However, short-term BrdU labelling showed that basal to suprabasal movement (leading to cell loss) occurred more rapidly in Pax6(+/-) than WT mice. This implies that epithelial cell loss is higher in Pax6(+/-) mice. If increased corneal epithelial cell loss exceeds the cell production capacity it could cause corneal homeostasis to become unstable, resulting in progressive corneal deterioration. Although it remains unclear whether Pax6(+/-) mice have LESC-deficiency, we suggest that features of corneal deterioration, that are often taken as evidence of LESC-deficiency, might occur in the absence of stem cell deficiency if corneal homeostasis is destabilised by excessive cell loss.